Three New Species of Deep-Sea Wood-Associated Sea Stars (Asteroidea: Caymanostellidae) from the Eastern Pacific - Shen, Zihui; Koch, Nicolás Mongiardino; Seid, Charlotte A.; Tilic, Ekin; Rouse, Greg W. (Zootaxa, 2024)
Caymanostellidae is a group of rarely collected and morphologically unusual sea stars that have been exclusively encountered on wood falls in the deep sea. There are currently three genera and seven species described, occurring in the Atlantic, Pacific and Indian Oceans with a depth range between 418 and 6780 m. Three new species are here described from specimens collected from wood falls in multiple localities across the Pacific margin of Costa Rica and near the Gulf of California (Mexico): Caymanostella scrippscognaticausa sp. nov., Caymanostella davidalani sp. nov. and Caymanostella loresae sp. nov. These records expand the known geographical distribution of caymanostellids and constitute their first report from wood falls found at methane seeps. This study also includes the first descriptions of early-stage juvenile caymanostellids and reveals that traits previously considered useful for diagnosis might represent intraspecific and ontogenetic variability, with important consequences for caymanostellid taxonomy.